TRANSFORMASI BUDAYA ORGANISASI PADA ERA DISRUPSI TEKNOLOGI DI PT. STRATEGIC PARTNER SOLUTION - Mey Luvita; Ahmad Toni (Universitas Prof. Dr. Moestopo (Beragama), 2022)
This study aims to contribute to changes in an organizational culture that is influenced by certain factors, such as in this study, namely because of the era of technological disruption and its changes towards digitalization, this research is a descriptive qualitative research with direct observation and in-depth interviews. and carried out within one year from September 1, 2020 to October 31, 2021 at PT Strategic Partner Solution. This research is a phenomenological research and uses Kurt Lewin's model (unfreezing, change and refreezing), and based on the results of this study indicate that the unfreezing process is a process of acceptance of changes that will be made to an organizational culture by all its members, then in the process of change. for implementation carried out by all members of the organization by carrying out their duties and obligations as well as being ambitious in the change process, and the last is the process of refreezing or integrating attitudes and behavior towards a new culture, of course the role of management is very important to provide support for every process of transformation carried out to enlarge opportunities for success in creating a new organizational culture.